Long Noncoding RNAs-Related Diseases, Cancers, and Drugs. (6th June 2013) - Tang, Jen-Yang; Lee, Jin-Ching; Chang, Yung-Ting; Hou, Ming-Feng; Huang, Hurng-Wern; Liaw, Chih-Chuang; Chang, Hsueh-Wei
Abstract : Long noncoding RNA (lncRNA) function is described in terms of related gene expressions, diseases, and cancers as well as their polymorphisms. Potential modulators of lncRNA function, including clinical drugs, natural products, and derivatives, are discussed, and bioinformatic resources are summarized. The improving knowledge of the lncRNA regulatory network has implications not only in gene expression, diseases, and cancers, but also in the development of lncRNA-based pharmacology.